Agile Software Development Using Cloud Computing: A Case Study - Younas, M. (Institute of Electrical and Electronics Engineers Inc., 2020)
Agile software development is successful due to self-organizing teams, adaptive planning, a cooperative environment with respect to communication with clients and team members, small development cycles, continuous design improvements, continuous delivery and feedback of clients. Cloud computing helps to reduce cost, enables scalability and enhances communication through its services. A generic framework with the conjunction of Agile Development and Cloud Computing (ADCC) proposed in an earlier study is evaluated in this study. The Malaysia Research and education network (MyRen) cloud is utilized to implement the framework. A case study is conducted to evaluate the framework. Before conducting the case study, the participants are educated on the ADCC framework. The results of the case study show that the performance of agile methods is improved with the usage of the ADCC framework. The improvement is measured in terms of local and distributed agile development environments. Â© 2013 IEEE.